Perbandingan Model Pembelajaran Thinks Pair Share (TPS) Dengan Model Numbered Heads Together (NHT) Terhadap Hasil Belajar Siswa Kelas X Di MA DA Jerowaru - Irwan Yon Hadi (Pendidikan Al-Gafari, 2024)
Education is business conscious and planned for realizing atmosphere learning and the learning process for participants educate in a way active develop potency himself for own religious spiritual power, control self, personality, intelligence, morals noble, as well necessary skills himself, society, nation, and state. Study This aims to know There are different results study students using a learning model think pair share (TPS) and numbered heads together (NHT) class X MA DA Jerowaru. Study This is a study experiment. The population is all over student class X MA DA Jerowaru. Research sample involving 2 classes totaling 75 students Class X MA DA Jerowaru is determined with a simple random sampling technique. Class XI totaling 36 students, was given treatment with a learning model thinks pair share (TPS), and temporary class X.II, totaling 39, was given treatment with a learning model numbered heads together (NHT). The research design used is a “post-test only design”. Data collection techniques were carried out with the use of method test subjective form essay. Whereas technique analysis of the data used for the test hypothesis is a two-party t-test (polled variance). The calculation of the results obtained amounted to 8.35 wheas mark t_tabelof 1.99 with a signifance level of 5%. Based on subcription tha result > then it can be concluded that Ho is rejected and Ha is accepted. It can be concluded that there are differences in student learning outcomes using the thinks pair share (TPS) and numbered heads together (NHT) learning models for class X MA DA Jerowaru.